Diagnosis and treatment of early stages of diabetic nephropathy - Efimov, A.S.; Tsymbal, T.S. (Reports of the National Academy of Sciences of Ukraine, 2014)
The concentration of TGF–β1 in blood serum of patients with type 1 diabetes mellitus with various stages of diabetic nephropathy (DN) is measured. 40 patients were conducted: 1 group – patients with DN of the 3-d stage diagnosed for the first time, 2 group – patients with DN of the 3-d stage in the anamnesis for the first time, 3 group – patients with diabetic nephropathy with duration macroalbuminuria, 4 group – patients without DN (positive control), 5 group – healthy volunteers (negative control).